The role of fire as a long-term landscape modifier: Evidence from long-term fire observations (1922–2000) in Greece. (September 2016) - Stamou, Zoi; Xystrakis, Fotios; Koutsias, Nikos
Abstract: The objective of this paper is to document the role of fire in shaping the landscape by identifying links between historical fire records and the current landscape indicating that fire favors certain land use/land cover (LULC) types. We geo-referenced fire records taken from 1922 to 2000 in Aitoloakarnania, the largest prefecture -in terms of surface area- of Greece and compared the past LULC classes where fires burned to the present landscape. The outputs indicated a shift of the historic fire ignition points from natural to agricultural-related LULC classes since a significant proportion of fire incidents that, according to the fire records, burnt natural vegetation units is currently located in agricultural landscape units. Additionally, a significant proportion of the fire-affected land cover classes retain their character thus supporting the argument that these classes, especially fire-prone or fire-resistant, have developed mechanisms to cope with fire. In such ecosystems the role of fire is to maintain rather than transform land cover classes. The findings of this research lead us to conclude that fire can be perceived as a long-term landscape modifier in the Mediterranean, although its effects may vary from region to region because of differences in regeneration patterns among the main land cover types, topographic constraints and local fire histories. Historical fire records extending back to the early 20th century proved to provide valuable information that can reveal interesting patterns of fire burning history and explain present land cover and use patterns. This knowledge, documented from historical records, can be used to develop fire management and land cover/land use management planning. Highlights: We geo-referenced fire records recorded from 1922 to 2000. There is a shift of the historic fire ignition points from natural to agricultural-related LULC classes. Fire can be perceived as a long-term landscape modifier in the Mediterranean. A significant proportion of the fire-affected land cover classes retains their character. In certain ecosystems the role of fire is to maintain rather than transform the land cover class.